Accessing a new molecular scaffold for Fe(II) spin state switching through first coordination changes - Livesay, Brooke N., author; Shores, Matthew P, advisor; Rappé, Anthony K., committee member; Van Orden, Alan, committee member; Ross, Kathryn A., committee member (Colorado State University. Libraries, 2021)
Presented in this dissertation are the syntheses and characterizations of iron spin state switching complexes. The magnetic properties are extremely sensitive to environmental changes such as ligand field, coordination environment, and crystal packing. These studies focus on developing a better understanding of how the magnetic properties of iron complexes can be controlled by environmental modifications. The first chapter provides a detailed introduction to spin state switching. The chapter includes the origins of the phenomenon and background into previous efforts to modify the spin switching event. This chapter highlights the challenges of designing a spin state switching complex and the different pathways used to induce spin switching events in the solid state and solution phase. Chapter 2 describes the procedures used to collect solution magnetic data. This chapter details the advantages of collecting solution data using a MPMS instrument compared to the Evans' (1H NMR) Method. The standard operating procedures for the method using a MPMS instrument are described for future researchers. Examples of solution magnetic data collected by both methods are described and compared. Chapter 3 discusses the challenges that were encountered during the synthesis of an iron(II) complex. The synthesis stopped producing the desired product after it was successful for several months. Investigations into the reproducibility, synthetic methods, and purification steps were performed to understand why the original synthetic procedure stopped working. This chapter describes how commercially-available starting materials can differ between lot numbers and manufacturers and how these small differences can lead to significant changes in the purity of the final product. Chapter 4 discusses the impact of speciation on the spin state switching properties of the neutral iron(II) compound synthesized in Chapter 3. Analysis in the solid state indicates the iron(II) complex is in the high spin state at all temperatures. When this compound is dissolved in strongly coordinating solvents the bound anions are replaced by the solvent resulting in a high spin species when the solvent is oxygen-donating and low spin species when the solvent is nitrogen-donating. In non-coordinating solvents the iron(II) complex loses one of the bound anions but remains high spin. However, in moderately coordinating solvents like acetone, the iron(II) loses the bound anions upon decreasing the temperature, resulting in a coordination induced spin state switching event. These studies highlight the sensitivity of solvent choice on the solution magnetic properties of iron(II) compounds. Chapter 5 discusses the thought process used to design the synthetic procedure for the post-synthetic modification of an iron(II) compound. The azide alkyne cycloaddition reaction was tested with several catalysts and deprotecting agents. Thoughtful consideration was taken to avoid the transmetallation reaction between the cycloaddition catalyst and the iron(II) compound. The successful reaction conditions for the post synthetic modification were found and resulted in the formation of the desired iron(II) triazole compound. Additional iron(II) triazole complex salts synthesized following the method described in Chapter 5 are described and characterized in Chapter 6. Electron-donating, electron-withdrawing, and oxidation-sensitive substituents are included on the iron(II) triazole ligand to show the scope of the post synthetic modification reaction and allow for investigation into how substituents effect the magnetic properties of the resulting compounds. Variable temperature solid state magnetic characterization indicates the resulting iron(II) compounds show a variety of magnetic behaviors. However, analysis of the crystallographic data and comparison to related previously published iron(II) triazole compounds indicate the differences in the magnetic properties are due to the solid state crystal packing effects. In Chapter 7 the solution magnetic properties of the iron(II) triazole compounds described in Chapter 6 are discussed. Removing the crystal packing effects by characterizing the compounds in solution allows for discovery of a relationship between the substituent properties and the magnetic behavior of the resulting compounds. The compounds were characterized in d4-CD4OD by Evans' 1H NMR method and show a thermal spin state switching event. However, no relationship between the Hammett parameter of the substituents and the spin state properties was observed. Chapter 8 summarizes the investigation of solvent induced spin state switching and post-synthetic modification. Additionally, I discuss some future work that would expand on the studies presented in this dissertation.
Keywords: spin state switching; magnetic properties; environmental change; MPMS instrument; iron(II) complex; iron(II) triazole